Original articleThe key role of sphingosine kinases in the molecular mechanism of neuronal cell survival and death in an experimental model of Parkinson’s disease - Pyszko, Joanna A.; Strosznajder, Joanna B. (Folia Neuropathologica, 2014)
Sphingosine kinases (Sphk1/2 EC 2.7.1.91) are responsible for synthesis of sphingosine-1-phosphate (S1P) and for regulation of the bioactive sphingolipids homeostasis. Sphingosine-1-phosphate can act as a potent messenger in an autocrine/paracrine manner through five specific G protein-coupled receptors (GPCR) S1P1-5. This sphingolipid is involved in the mechanism of transcription, mitochondrial function, neuronal viability and degeneration. Until now the involvement of Sphk1/2 and sphingolipid alterations in Parkinson’s disease (PD) remains unknown. Recent studies have indicated the role of sphingolipids in the regulation of alpha-synuclein (ASN) in the PD brain. Our latest data demonstrated significant inhibition of Sphk1 gene expression and activity in an in vitro PD model, induced by 1-methyl-4-phenylpyridinium (MPP+). The aim of this study was to investigate the role of Sphks inhibition in ASN secretion and in the molecular mechanism of neuronal death in the PD model. Our study was carried out using neuronal dopaminergic SH-SY5Y control cells, transfected with the human gene for ASN or with an empty vector. These cells were treated with MPP+ (1-3 mM), which represents an experimental PD model, or with the Sphks inhibitor (1-5 µM SKI II) for 3-24 h. Our data indicated that MPP+ (3 mM) induced significant alterations of Sphks and S1P lyase (SPL) gene expression. Reduced activity of Sphk1 and Sphk2 in the cytosolic fraction and in the crude nuclear fraction, respectively, was observed. Sphks inhibition evoked enhancement of ASN secretion, suppression of PI3K/Akt phosphorylation and activation of gene expression for the pro-apoptotic Bcl-2 proteins Bax and BH3-only protein Harakiri. Moreover, a lower level of cytochrome c in the mitochondrial fraction and caspase-dependent degradation of DNA-bound enzyme poly(ADP-ribose) polymerase (PARP-1) were observed. The caspase inhibitor (20 µM Z-VAD-FMK) significantly enhanced neuronal cell viability in MPP+ oxidative stress. However, exogenous S1P (1 µM) exerted a more efficient neuroprotective effect as compared to Z-VAD-FMK. In summary, these data indicated that Sphk1 inhibition plays an important role in caspase-dependent apoptotic neuronal death in an experimental PD model.